A dynamic poroelastic model for auxetic polyurethane foams involving viscoelasticity and pneumatic damping effects in the linear regime. (1st November 2022) - Zhang, Qicheng; Yu, Xindi; Scarpa, Fabrizio; Barton, David; Zhu, Yunpeng; Lang, Zi-Qiang; Zhang, Dayi
Abstract: This work proposes a new dynamic poroelastic model to describe the vibration transmissibility of auxetic polyurethane (PU) foams. The model includes the pneumatic damping effect provided by the porous structure of the foam, and the viscoelasticity of the PU material. The auxetic foam is manufactured using a simplified and relatively low-cost uniaxially thermoforming compression technique, which allows the production of a foam with transverse isotropic properties. Stress relaxation, quasi-static cyclic compressive-tensile and seismic base vibration tests in the small strains and linear elastic regimes have been performed in this work. The permeability and the viscoelasticity of the auxetic foams with different thermoforming compression ratios along the thermoforming and transverse directions are identified by performing a nonlinear regression from the mechanical and vibration-derived data. The auxetic foams possess lower stiffness along the thermoforming direction and higher modulus along the transverse one. The moduli of different auxetic foams obtained from quasi-static tests are 40%–70% lower than the corresponding dynamic values estimated from the seismic base excitation, while the static loss factors are all around 20%–100% lower than the corresponding dynamic ones. The enhancements of the dynamic stiffness and damping are mainly caused by the pneumatic damping effect and the viscoelasticity of the PU material. The permeability of the auxetic foam loaded along the thermoforming direction is ∼ 2 times larger than the one of the pristine foam, but 50% smaller when the foam is dynamically loaded along the transverse direction, due to the transverse isotropic microstructure of this porous material.